Vinculaç\~ao orçamentária do gasto em saúde no Brasil: Resultados e argumentos a seu favor - Fabiola Sulpino Vieira; Sérgio F. Piola; Rodrigo Pucci de Sá e Benevides (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Allocating sufficient resources to the Unified Health System (SUS) is a basic premise for compliance by the State with its duty to guarantee universal, equal and integral access to health goods and services in Brazil. As a way of ensuring minimal resources to the system, the compulsory expenditure with health was instituted. Recently, amid the fiscal crisis and the changes in the political environment in the country, the extinction of this compulsory expenditure is considered. In this context, the objective of this paper is to present evidence and discuss the relevance of maintaining the compulsory public health expenditure, thus contributing to the public debate on the topic. A narrative review of the technical-scientific literature and legal documents was performed to organize the discussion on the subjects treated in two perspectives: i) a historical perspective on the regulation of the minimum application of resources in the SUS, including in the report the propositions that weren't approved and the motivations for this regulation; and ii) a theoretical-empirical perspective on the hypothesis that universal public health systems, such as the SUS, and the compulsory health expenditure in Brazil are relevant to the right to health as determined by the Federal Constitution of 1988 (CF/1988). Considering the evidence presented about the lack of priority with the system and, consequently, with the guarantee of the right to health in Brazil, the conclusion is that the compulsory health expenditure remains essential. Even so, this obligation alone does not solve the financing problem of the system, since in spite of the institution of the floors of application from 2000, health expenses are still very low compared to those countries with similar income and who do not have a universal health system. However, it is an important mechanism to protect against throwback in the supply of health goods and services, something that is forbidden by CF/1988. The stability in the financing of the SUS is fundamental and the compulsory health expenditure fulfilled vital role, considering the trajectory of public health financing. Nonetheless, the country needs to make an additional effort to guarantee sufficient resources to finance the SUS, given the challenges posed to the system stemming from epidemiological, demographic and technological issues that drive the growth of health spending.
Keywords: H51; 330; healthcare financing; health expenditures; universal access to health care services; right to health; national health systems; Unified Health System